A heuristic approach for in-pit crusher and conveyor system's time and location problem in large open-pit mining. Issue 1 (2nd January 2018) - Paricheh, Morteza; Osanloo, Morteza; Rahmanpour, Mehdi
Abstract: Cost efficiency and high reliability of In-Pit Crushing and Conveying (IPCC) system make it more appealing to be used in deeper open-pit mining activities. Determination of the optimum time and location (OT–OL) for applying the IPCC system were always a challenge. Application of mathematical programming approaches suffers from reduced computational efficiency due to a lot of decision variables. The situation will be worse; by adding the IPCC's time and location variables to these models. Also, the problem involves a lot of variables that each one of them is a function of others. To tackle these, this paper provides a new heuristic approach to find a good quality solution hierarchically (here in two levels). The problem was broken into two parts (i.e. OT and OL). The model works in a discrete time horizon. It has been verified by the data gathered from Sungun copper mine of Iran. Our computational results show that the system is efficient for developed countries with a stable and low interest rate.